High-rate balanced space-time block code selection - Sahin, Selami; Aygolu, Umit (IEEE, 2008)
In this paper, the rate of full-rate balanced space-time block code selection scheme (BSTBCS) is increased by power scaling without decreasing the diversity order. As a simple case, for the balanced code pair with three transmit antennas, the optimum power scaling factor is obtained theoretically to maximize the coding gain (CG) and to minimize the peak-to-minimum power ratio (PMPR). By computer simulations, it is shown that the loss in CG with rate increasing of one bit feedback BSTBCS scheme is 0.6 dB lower than that of the high-rate scheme using Alamouti code. Moreover, effective throughput of high-rate systems are greater than that of their full-rate counterpart over a signal-to-noise ratio (SNR) threshold. It is shown by computer simulations that this threshold level is 1.4 dB lower when BSTBCS scheme with one bit feedback is used instead of Alamouti code. In addition, Alamouti code achieves the same threshold when used cooperatively with transmit antenna selection (TAS) scheme which needs two feedback bits.